Perilaku Pengelolaan Keuangan Mahasiswa Kost UMS: Peran Mental Accounting, Self-Control dan Moderasi Literasi Keuangan - Musthofa Sidiq; Sabar Narimo (Owner : Riset dan Jurnal Akuntansi, 2026)
Drawing on behavioral finance and self-regulation theories, this study investigates the impacts of mental accounting and self-control on the financial management behavior of university boarding students, while evaluating the moderating role of financial literacy. Utilizing a quantitative causal-associative design, data were gathered via online questionnaires using purposive sampling from 136 students at Universitas Muhammadiyah Surakarta (UMS) who independently manage their finances. Data analysis was executed through Partial Least Squares-Structural Equation Modeling (PLS-SEM). The empirical results reveal that both mental accounting and self-control exert positive and significant direct effects on students’ financial behavior. Crucially, although financial literacy directly influences financial management, it fails to operate as a moderator across all pathways. The structural model demonstrates high explanatory power, accounting for 71.4% of the variance (R² = 0.714). These insights unearth a critical knowledge-to-action gap, indicating that under financial constraints, students’ decisions are governed by immediate self-regulation mechanisms and adaptive survival strategies rather than formal knowledge. Practically, institutional financial education programs must pivot from conventional theoretical curricula toward behavioral-based training and real-life simulations.